ACCURACY OF IDIOM TRANSLATION IN SIDNEY SHELDON’S THE SKY IS FALLING INTO INDONESIAN LANGIT RUNTUH - Wulan Yulian Anggini (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2019)
The purpose of this research is to know the accuracy of idiom translation and strategies that are used by the translator in translating the idiom into Bahasa Indonesia. This research uses qualitative descriptive analysis. After analyzing the results of accuracy of idiom translation from the three evaluators in the novel entitled The Sky is Falling, the researcher gets the conclusion that accuracy in “0” scale takes the highest position. There are three strategies used by the translator in translating idioms. They are paraphrase which marks 87%, borrowing the source language idioms with 6%, omission of entire idioms with 2%, using an idiom of similar meaning but dissimilar form with 5%.Keywords: Accuracy, Idiom Translation, Novel entitled The Sky is Falling.